EFEKTIVITAS PENYULUH PERTANIAN DALAM MENINGKATKAN PENDAPATAN PETANI JAGUNG HIBRIDA DI KOTA PAREPARE - Haslinda, Haslinda; Toha, Sahabuddin; Ambar, Abdul Azis (Universitas Negeri Makassar, 2019)
This study aims to determine the effectiveness of agricultural extension workers in increasing the income of hybrid corn farmers in the city of Parepare. This study uses qualitative methods with data collection techniques consisting of observation, interviews, questionnaires and documentation. The number of respondents is 100 people from the total number of hybrid corn farmers in this region. The results obtained based on two indicators of efficiency, it is known that agricultural extension agents play an effective role in increasing the production and income of respondents.